Histological Assessment of Aqueous Solution of Hibiscus sabariffa calyx (Zobo drink) on the Frontal Cortex and Hippocampus of Albino Wistar Rats - Ujah, Williams Oche; Acha, Ozzioma Praise; Ayara, Charles; Makanjuola, Victor; Agaba, Eric Agim; Williams, Queen Uyo; Akafa, Tensaba Andes; Umaru, Isaac John (African Journal of Clinical Medicine and Pharmacy Research, 2024)
Zobo drink which is consumed by many Nigerians, is a non-alcoholic beverage with phytoactive properties. This study investigated the histological outcome of Hibiscus sabdariffa calyx aqueous solution (Zobo drink) on the frontal cortex and hippocampus of albino wistar rats. Twenty (20) albino wistar rats were used, and grouped into a control group A, B, C, D and E. Group A was the control group. 0.5ml of Zobo drink was administered at different time interval to the experimental groups for 21 days. Zobo drink was administered to group B once a day, two times a day to group C, three times a day to group D and throughout the duration of administration to group E. In the end, the rats were sacrificed and the brain was removed and fixed in 10% formal saline solution. The frontal cortex and hippocampus were stained with Haematoxylin and eosin. Results show that no adverse effect on the frontal cortex of group B, C, D and E but shows effect on group E which is the high dose.